PENERAPAN MEDIA ARTICULATE STORYLINE DALAM PEMBELAJARAN NITISASTRA PADA MATA KULIAH AGAMA HINDU - Ni Nyoman Tri Thika Dewanthari; I Wayan Eka Santika (Bajang Institute, 2025)
The purpose of this research is to determine the usefulness of the articulate storyline media in helping students understand complex nitisastra concepts in the Hindu Religion course at the Electrical Engineering Department of Bali State Polytechnic. The method used was qualitative research, and data were collected through interviews, observations, and document analysis. The research results show that the use of articulate storyline significantly increases student engagement, makes the material easier to understand, and reduces boredom during the learning process. Students said that they felt more motivated and achieved positive learning outcomes after using this media. In the field of education, the results of this research are expected to provide new insights into the use of technology in teaching nitisastra. And the author does not forget to provide suggestions for the development of a more creative curriculum. Because, with the use of creative and interactive media in the teaching of nitisastra, it not only helps students learn more about the material being presented but also shapes their character and ethics as they understand the learning material being conveyed. Therefore, the use of articulate storyline can be a strategic step to improve the quality of education in the current digital era